Genetic variations in key microRNA processing genes and risk of head and neck cancer: a case-control study in Chinese population. - Hongxia Ma; Hua Yuan; Zhiyao Yuan; Chenjie Yu; Ruixia Wang; Yue Jiang; Zhibin Hu; Hongbing Shen; Ning Chen (PLoS ONE, 2012)
MicroRNAs (miRNAs) have been reported to play a key role in oncogenesis. Genetic variations in miRNA processing genes and miRNA binding sites may affect the biogenesis of miRNA and the miRNA-mRNA interactions, hence promoting tumorigenesis. In the present study, we hypothesized that potentially functional polymorphisms in miRNA processing genes may contribute to head and neck cancer (HNC) susceptibility. To test this hypothesis, we genotyped three SNPs at miRNA binding sites of miRNA processing genes (rs1057035 in 3'UTR of DICER, rs3803012 in 3'UTR of RAN and rs10773771 in 3'UTR of HIWI) with a case-control study including 397 HNC cases and 900 controls matched by age and sex in Chinese. Although none of three SNPs was significantly associated with overall risk of HNC, rs1057035 in 3'UTR of DICER was associated with a significantly decreased risk of oral cancer (TC/CC vs. TT: adjusted OR  =  0.65, 95% CI  =  0.46-0.92). Furthermore, luciferase activity assay showed that rs1057035 variant C allele led to significantly lower expression levels as compared to the T allele, which may be due to the relatively high inhibition of hsa-miR-574-3p on DICER mRNA. These findings indicated that rs1057035 located at 3'UTR of DICER may contribute to the risk of oral cancer by affecting the binding of miRNAs to DICER. Large-scale and well-designed studies are warranted to validate our findings.